Measuring Debt Effectiveness of the Companies with the Highest Score of FSA/OJK Version in Indonesia (Financial Services Authority/Otoritas Jasa Keuangan) - Indahwati Indahwati; Ni Ketut Yulia Agustini; Dana Aditya (Budapest International Research and Critics University, 2022)
Debt issues are a serious concern for companies especially related to the risk of interest and debt repayment when due. This is experienced by 7 companies in Indonesia who defaulted on debt in 2019. On the other hand, there are 50 companies that achieverd the highest score of FSA/OJK (Otoritas Jasa Keuangan) version, althought many of them have very high debts. This study aims to examine the use of debt and the risk of using debt of these companies, so that they are able to control their debt uses. Population of this study are taken from the companies with the highest score of OJK version from 2016 to 2019, samples are taken with purposive sampling by issuing the financial industries. Data analyzing technique used is path analysis using 2 exogenous variables namely the use of debt (leverage) and the risk of using debt (degree of leverage) and 1 variable endogeous namely the debt effectiveness (ROA). This study founds that the use of debt of these companies is effective, it is proven that the use of debt and its risks interact to increase profitability (ROA). Further more this research in line with the study by Indahwati and R. Suryasaputra, 2019.